Growing faster, longer or both? Modelling plastic response of Juniperus communis growth phenology to climate change. Issue 11 (18th August 2021) - Tumajer, Jan; Buras, Allan; Camarero, J. Julio; Carrer, Marco; Shetti, Rohan; Wilmking, Martin; Altman, Jan; Sangüesa‐Barreda, Gabriel; Lehejček, Jiří
Abstract: Aim: Plant growth and phenology respond plastically to changing climatic conditions in both space and time. Species‐specific levels of growth plasticity determine biogeographical patterns and the adaptive capacity of species to climate change. However, a direct assessment of spatial and temporal variability in radial growth dynamics is complicated, because long records of cambial phenology do not exist. Location: Sixteen sites across European distribution margins of Juniperus communis L. (the Mediterranean, the Arctic, the Alps and the Urals). Time period: 1940–2016. Major taxa studied: Juniperus communis . Methods: We applied the Vaganov–Shashkin process‐based model of wood formation to estimate trends in growing season duration and growth kinetics since 1940. We assumed that J. communis would exhibit spatially and temporally variable growth patterns reflecting local climatic conditions. Results: Our simulations indicate regional differences in growth dynamics and plastic responses to climate warming. The mean growing season duration is the longest at Mediterranean sites and, recently, there has been a significant trend towards its extension of up to 0.44 days/year. However, this stimulating effect of a longer growing season is counteracted by declining summer growth rates caused by amplified drought stress. Consequently, overall trends in simulated ring widths are marginal in the Mediterranean. In contrast, durations of growing seasons in the Arctic show lower and mostly non‐significant trends. However, spring and summer growth rates follow increasing temperatures, leading to a growth increase of up to 0.32 %/year. Main conclusions: This study highlights the plasticity in growth phenology of widely distributed shrubs to climate warming: an earlier onset of cambial activity that offsets the negative effects of summer droughts in the Mediterranean and, conversely, an intensification of growth rates during the short growing seasons in the Arctic. Such plastic growth responsiveness allows woody plants to adapt to the local pace of climate change.